2020
DOI: 10.3390/jof6040272
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of a Novel ABL (Abnormal Browning Related to Light) Gene in Mycelial Brown Film Formation of Lentinula edodes

Abstract: Lentinula edodes is a globally important edible mushroom species that is appreciated for its medicinal properties as well as its nutritional value. During commercial cultivation, a mycelial brown film forms on the surface of the sawdust growth medium at the late vegetative stage. Mycelial film formation is a critical developmental process that contributes to the quantity and quality of the mushroom yield. However, little is known regarding the genetic underpinnings of brown film formation on the surface of myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Browning, a critical developmental process that contributes to the quantity and quality of L. edodes production, largely affects resistance potential against disease and insect, yield, and number of fruiting flushes [15]. Our study suggested that partly substituting corncob for sawdust promoted log browning.…”
Section: Effect Of Substrate Formula On Mycelia Growth Log Browning and Mushroom Yieldmentioning
confidence: 66%
“…Browning, a critical developmental process that contributes to the quantity and quality of L. edodes production, largely affects resistance potential against disease and insect, yield, and number of fruiting flushes [15]. Our study suggested that partly substituting corncob for sawdust promoted log browning.…”
Section: Effect Of Substrate Formula On Mycelia Growth Log Browning and Mushroom Yieldmentioning
confidence: 66%
“…Similarly, the blue light and its receptor white collar complex coding genes FfWc1 and FfWc2 in F. filiformis can regulate the role of morphogenesis [185]. In addition, Gf.BMR1 from G. frondosa contributes to fruiting body development and pigment accumulation [186], abl-D from L. edodes promotes the formation of brown film in mycelia [187], and Pabs from A. bisporus [188] enhances UV tolerance. These studies can provide references for light control in the production of edible and medicinal fungi in factories.…”
Section: Genes Related To Environmental Responsementioning
confidence: 99%
“…Next-generation sequencing technologies have been widely used to study plant pathogens and greatly facilitated understanding of fungal evolution and virulence factors [ 22 , 23 , 24 , 25 , 26 , 27 ]. The lifestyle of fungal species in Dothideomycetes evolves in four major transitions from non-phytopathogenic to phytopathogenic, along with the pathogenicity-related genes carried in different genera varying considerably [ 28 ].…”
Section: Introductionmentioning
confidence: 99%